Gamificação e o desenvolvimento da competência diagnóstica: uma revisão sistemática da literatura - BENTO, Cristiano José (2019)
Gamification is the use of game elements in various environments, from simple fun to education. It has been a resource increasingly used in several fields of knowledge and shows itself as a great promise in health education, for its potential to increase intrinsic motivation and encourage collaboration and competition among students, which may favor diagnostic competence. Diagnostic Competence can be defined as the expertise to perform clinical diagnoses correctly in a real setting, using the theoretical knowledge and skills acquired along the medical path, which depends on the development of adequate clinical reasoning. There are still many gaps in knowledge about the relationship between diagnostic competence and the use of gamification, although different studies indicate positive effects of this relationship. Objective: To investigate the relationship between the use of gamification and the development of clinical reasoning and diagnostic competence in medical students. Materials and methods: We conducted a systematic review of the literature guided by the descriptors: medical studants, educational games, medical education, mack decision, educational games assessment, clinical reaseons, clinical competences, diagnostic accuracy diagnostic competence, collaborative learning, Boolean operators (AND, NOT and OR), in 130 databases gathered in a single interface in the virtual library called Portal Capes, of the Brazilian Ministry of Education. The period of the search was delimited between 2008-2018, selecting the scientific studies of experimental design. Results: From a total of 1040 articles selected by the titles, 499 were screened through the abstracts being considered eligible 15 studies, which after analysis of the methodology, were restricted to only four for summarization. All studies were from neutral to positive in relation to knowledge gain and clinical reasoning, with better decision making in the gamification group. All the studies were positively evaluated by the participants through satisfaction questionnaires. The risk of bias was moderate, with good methodological quality assessed by the MERSQI score. Conclusion: The use of gamification points to positive results to favor clinical reasoning and decision making and can be used as promising instructional strategy. More robust studies may confirm this trend